The Illustrated Encyclopedia of 20th Century Weapons and Warfare (Vol.18) - Edited By Fitzsimons, Bernard (New York Columbia House, 1978)
Any profound understanding of the wars which have shaped our world depends on an understanding of the weapons with which they were fought. In these volumes, details of all the weapons of our century are gathered together in a single work. The facts and information packed into these magnificent volumes could only be duplicated in a library of reference works, and even then, so thorough has been the work of the contributors that new facts are constantly being brought to light, new theories advanced and old myths exploded."
Include Color Illustrations and Tables
24 Volumes
Keywords: Military art and science -- Military weapons -- Arms and armor